Unjuk Kinerja Alat Pasteurisasi pada Proses Pasteurisasi Madu: Studi Kasus PT Kembang Joyo Sriwijaya - Wibowo, Sasongko Aji; Lastriyanto, Anang; Erwan, Erwan; Jaya, Firman; Batoro, Jati (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2021)
One of the post-harvest honey processing processes is the pasteurization process. Pasteurization is the initial stage of honey processing before evaporation. The high demand for honey in Indonesia requires that honey producing companies must use pasteurization tools with large capacities and do not damage the honey content. Honey will be damaged if the pasteurization temperature is more than 70oC. In addition, the pasteurization process is also still a problem in the honey industry. Therefore it is necessary to make pasteurization tools with automatic and fast temperature control in the pasteurization process. The purpose of this study was to observe the rate of heat penetration into pasteurized honey material and the amount of honey weight pasteurized, then also measured changes in water content, viscosity, degree Brix, and density of density. From the results of measurements of heat penetration rates in pasteurization and conventional pasteurization devices, the difference in time duration on stoves 1, 2, and 3 to increase the initial temperature of 35 oC to 65oC respectively were 45, 45, and 42 minutes with a total of 101 honey, 22 kg while in conventional equipment takes 50 minutes to heat honey as much as 46,780 kg. Gas consumption on stove 1 was 0.291 g/(kgoC), stove 2 was 0.281 g/(kgoC), stove 3 was 0.285 g / (kgoC), whereas gas consumption on conventional stove was 0.272 g/(kgoC). The results of measurements of water content, viscosity, Brix, and density of density before and after pasteurization were as follows 21.99%, 4.835 poise, 63 obrix, 1.356 kg/m3, and 19.82%, 5.453 poise, 64 obrix, 1.358 kg/m3.